2022
DOI: 10.3389/fmicb.2022.922324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of graphene oxide, chitosan and their complex as antibacterial agents and anticancer apoptotic effect on HeLa cell line

Abstract: Cancer and bacterial infection are the most serious problems threatening people's lives worldwide. However, the overuse of antibiotics as antibacterial and anticancer treatments can cause side effects and lead to drug-resistant bacteria. Therefore, developing natural materials with excellent antibacterial and anticancer activity is of great importance. In this study, different concentrations of chitosan (CS), graphene oxide (GO), and graphene oxide-chitosan composite (GO-CS) were tested to inhibit the bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Electrostatic interaction and hydrogen bonding due to the presence of a carboxylic group in the ChGA chain contributed to depressing the RSC96 cells. Other studies in carboxylated Ch have shown that all in vitro evaluations demonstrated good cell viability 76–78 . Nevertheless, a cell viability percentage of more than 70% indicates a non‐cytotoxic compound according to ISO 10993‐5 79 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Electrostatic interaction and hydrogen bonding due to the presence of a carboxylic group in the ChGA chain contributed to depressing the RSC96 cells. Other studies in carboxylated Ch have shown that all in vitro evaluations demonstrated good cell viability 76–78 . Nevertheless, a cell viability percentage of more than 70% indicates a non‐cytotoxic compound according to ISO 10993‐5 79 .…”
Section: Resultsmentioning
confidence: 97%
“…The cell viability percentage for Ch treatment was also high at 93.45 shown that all in vitro evaluations demonstrated good cell viability. [76][77][78] Nevertheless, a cell viability percentage of more than 70% indicates a non-cytotoxic compound according to ISO 10993-5. 79 Additionally, the addition of BPA in Ch-BPA and ChGA-BPA films may increase cell viability because of its characteristic as an antioxidant that can prevent oxidative stress from decreasing cell viability.…”
Section: Biodegradability and Cytotoxicity Testingmentioning
confidence: 99%
“…Importantly, blends of these copolymers with CG show greater growth inhibition than the copolymers themselves and are 5.81 log10 CFU/ml dCsSB-PCA-ε-CL: CG 50:50 and 5.96 log10 CFU/ml CsSB-SFD-ε-CL: CG 50:50. Despite many literature reports proving the antibacterial activity of chitosan and carrageenan [59,[80][81][82][83][84] only a slight decrease in the growth of the E. coli strain was observed at concentration 0.1mg/mL. The antibacterial activity of this strain after 48 h is shown in Figure S1 Supplementary Materials.…”
Section: Antibacterial and Antifungal Evaluationmentioning
confidence: 91%
“…Importantly, blends of these copolymers with CG show greater growth inhibition than the copolymers themselves and are 5.81 log 10 CFU/ml dCsSB-PCA-ε-CL: CG 50:50 and 5.96 log 10 CFU/ml CsSB-SFD-ε-CL: CG 50:50. Despite many reports in the literature proving the antibacterial activity of chitosan and carrageenan [59,[79][80][81][82][83], only a slight decrease in the growth of the E. coli strain was observed at concentration 0.1 mg/ml. The antibacterial activity of this strain after 48 h is shown in Figure S1 Supplementary Materials.…”
Section: Antibacterial and Antifungal Evaluationmentioning
confidence: 92%
“…In Figure S2 Supplementary Materials the results after 48 h are presented, they also show no significant changes compared to 24 h. inhibition than the copolymers themselves and are 5.81 log10 CFU/ml dCsSB-PCA-ε CG 50:50 and 5.96 log10 CFU/ml CsSB-SFD-ε-CL: CG 50:50. Despite many reports in literature proving the antibacterial activity of chitosan and carrageenan [59,[79][80][81][82][83], on slight decrease in the growth of the E. coli strain was observed at concentration 0.1 mg The antibacterial activity of this strain after 48 h is shown in Figure S1 Supplemen Materials. The results were similar to those after 24 h. The results regarding antibacterial activity against P. aeruginosa are presente Figure 12.…”
Section: Antibacterial and Antifungal Evaluationmentioning
confidence: 93%